Sermons That Have Changed My Life: A Qualitative Study of the Factors in Sermons that Elicit Change (Homiletic, 2019)
Can people be changed by sermons? This study focuses on the impact sermons can have on people’s lives, and the factors involved. A qualitative study was conducted among a group of sermon listeners. The results show that all the respondents experienced a change in their lives through sermons. Moreover, the respondents show remarkable unity in their views about which factors in the sermons caused them to change. The results illustrate that the connection between the message of the sermon and the actual question, the listener’s challenge or field of interest, and the preacher’s ability to communicate in a surprising and novel way are key factors in a sermon to elicit change.